PTU-084 The use of panoramic capsule endoscopy in obscure gastrointestinal bleeding. (June 2019) - Zammit, Stefania Chetcuti; McAlindon, Mark E; Sidhu, Reena
Abstract : Introduction: Up to 64% of patients with obscure gastrointestinal bleeding (OGIB) have lesions that can be reached with a standard gastroscope [1]. Positive findings outside the small bowel (SB) have been detected on axial small bowel capsule endoscopy (SBCE) (PillCam system, (Given Imaging) in patients with OGIB in up to 22% of patients in the stomach and 6% in the colon [2]. Our aim was to assess the diagnostic yield (DY) of panoramic SBCE (Capsocam) for the upper gastrointestinal tract, SB and colon in patients with OGIB. Methods: Patients at a tertiary centre who underwent Capsocam as part of the examination of OGIB following negative gastroduodenoscopy and colonoscopy or CT colonography were included. This study was carried out over a 6 year period. Findings on SBCE were recorded. Results: Forty-eight patients (37, 77.1% overt, 11, 22.9% occult OGIB) were included in this study. Thirty (62.5%) were males. Mean age was 67.5±16.5 years. OGIB was present for a mean of 19.9 SD±92 months. Only one SBCE (9.1%) was incomplete within the occult OGIB group (p=0.229). The panoramic SBCE had a diagnostic yield of 37.5% (18 patients) in the SB. It also picked up additional findings in the stomach (n=5, 10.4%) and in the colon (n=3, 6.3%). Some patients had more than one pathology (table 1 ). Conclusions: Panoramic SBCE can be useful in the detection of lesions in the stomach and colon missed during upper and lower gastrointestinal examinations. It can also be better in the detection of pathologies in overt OGIB than in occult OGIB. References: Zaman A, Katon RM: Push enteroscopy for obscure gastrointestinal bleeding yields a high incidence of proximal lesions within reach of a standard endoscope. Gastrointest Endosc 1998, 47:37–76. Riccioni ME, Urgesi R, Cianci R, Marmo C, Galasso D, Costamagna G: Obscure recurrent gastrointestinal bleeding: a revealed mystery? Scand J Gastroenterol 2014, 49:102–026.